Malaysian Tamils and transnational Tamil cinema : diasporic identities, 'Crisis Heterotopia' and 'Aura' / Gopalan Ravindran - Ravindran, Gopalan (UPENA, 2008)
Increasingly, the processes of globalisation and transnationalisation are proving to be crucial for the negotiations of transnational Tamil cinema and its diasporic audiences in more ways than one. In recent times, transnational Tamil cinema has expanded its territory beyond the shores of traditional diasporic markets in Singapore, Sri Lanka and Malaysia. It now caters to new and expanding markets such as South Africa, Japan, North America and Western Europe, besides its traditional diasporic markets. In a similar fashion, more than ever before, the identities of diasporic Tamils are being greatly impacted by the transnational Tamil cinema and its counterparts in other media. The processes of globalisation and transnationalisation have also caused the emergence of new sites of diasporic identity negotiations. These new sites are as much heterotopic and auratic as crisis ridden and non-auratic. This paper employs the notions of Michel Foucault and Walter Benjamin to examine the negotiations of identities by Malaysian Tamils in the sites constructed by transnational Tamil cinema.